Modifying actor-network theory to analyse the German project of photovoltaic electrical energy generation - Ray Galvin (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2009)
German state subsidies for photovoltaic (PV) electricity generation now amount to over 200 million euros per month. Yet PV in Germany is only 30% as economically efficient as wind power, while up to 19 times as much energy would be saved if the same funds were used to thermally renovate homes. The generous subsidy has led to increasing demand for PV units and an annual increase in subsidies of around 50%. This study investigates why these subsidies were instigated and why they continue. Because both material and social factors appear to play a role, a composite analytical framework is developed, using actor-network theory (ANT) and policy discourse approaches. This is achieved through discarding ontologically unsound concepts of radical human/non-human symmetry in ANT, while re-materialising the concept of discourse, and theorising how to test the veracity of strands in discourse which make truth claims about the material world. The result shows that the German PV subsidy system can be explained in terms of various interplays of material and discursive factors which have held sway in it at crucial times, from its inception to the present day.
Keywords: 330; photovoltaic; Germany; actor-network theory; discourse; Photovoltaikanlage; Förderung regenerativer Energien; Techniksoziologie; Deutschland